Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Fresno County Bar Association President Robert Oliver presenting plaque to Kathy Hart; Doug Jensen applauding 5080 E. Kings Canyon Road, Fresno